Effectiveness of Teleophthalmology As Diabetic Retinopathy Screening Modalities: Literature Review - Cattleya Ananda Vilda; Dumilah Ayuningtyas (Budapest International Research and Critics University, 2022)
The high risk of transmission through eye examinations in the COVID-19 pandemic has resulted in teleophthalmology usage in diabetic retinopathy screening programs. This review assesses the effectiveness of teleophthalmology for diabetic retinopathy screening. This literature review uses Pubmed, Proquest, and GoogleScholar as sources. Screening using inclusion and exclusion criteria has been included in 7 articles for review. Results Teleophthalmology increases the number of diabetic retinopathy cases finding on diabetes mellitus, resulting in high patient satisfaction and low cost. Teleophthalmology showed its effectiveness as a screening program for diabetic retinopathy in the era of the COVID-19 pandemic.